Interação silício e alumínio em plantas de arroz de terras altas e mamona - Freitas, Lucas Barbosa de [UNESP] (2015)
The aluminum toxicity is a major limiting productivity in acid soils and Si is an interesting way to minimize the Al3+ toxicity in plants, however, the mechanism of this interaction between Si and Al3+ is not well understood. The objectives underlying this work were: evaluate the efficiency of aluminum sources and doses in causing toxicity in upland rice plants grown in nutrient solution; describe the susceptibility to Al3+ by upland rice cultivars currently used by Brazilians farmers; describe the susceptibility of castor bean cultivars of FCA - UNESP' plant breeding program; evaluate the interaction between Si and Al3+ in upland rice plants (Si-accumulator plant) and castor bean (non-Si-accumulator plant). Were installed five greenhouse experiments, conducted in nutrient solution. All experiments were laid out in randomized block design, with four replications. Experiment 1 - arranged in factorial design 2x4, the treatments were two Al3+ source (aluminum sulfate and aluminum chloride) and five Al3+ doses (0; 370; 740; 1100 and 1480 μmol L-1) evaluated in upland rice plants. Experiment 2 - arranged in factorial design 2x9, the treatments were with and without Al3+ and nine upland rice cultivars. Experiment 3 - arranged in factorial design 2x9, the treatments were with and without Al3+ and nine castor bean cultivars. Experiment 4 - arranged in factorial design 2x4, the treatments were two upland rice cultivars (Maravilha Al3+ susceptible and ANa 7007 Al3+ tolerant) and four Si e Al3+ combinations (1-without Si and without Al3+; 2-with Si and without Al3+; 3- without Si and with Al3+, 4-with Si and with Al3+). Experiment 5 - arranged in factorial design 2x4, the treatments were two castor bean cultivars (CRZ H18 Al3+ susceptible and CRZ H06 Al3+ tolerant) and four Si e Al3+ combinations (1-without Si and without Al3+; 2-with Si and without Al3+; 3- without Si and with Al3+, 4-with Si and with Al3+) ...